A noble madness : the dark side of collecting from antiquity to now - Delbourgo, James, 1972- (W. W. Norton & Company, 2025)
"A captivating history of obsessive collectors: from ancient looters and idolaters to fin de siècle decadents, Freudian psychos, and hoarders. Collectors are often praised for their taste in art or contributions to science, and considered great public benefactors. But collectors have also been seen as dangerous obsessives who love objects too much. Why? From looters and idolaters to fin de siècle decadents and Freudian psychos, A Noble Madness is a captivating history of obsessive collectors from ancient times to today. From Roman emperors lusting after statues to modern-day hoarders, award-winning author James Delbourgo tells the extraordinary story of fanatical collectors throughout history. He explains how the idea first emerged that when we look at someone's collection, we see a portrait of their soul: complex, intriguing, yet possibly insane. What Delbourgo calls 'the Romantic collecting self' has always lurked on the dark side of humanity. But this dark side has a silver lining. Because obsessive collectors are driven by passion, not profit, they have been countercultural heroes in the modern imagination, defying respectability and taste in the name of truth to self. A grand portrait gallery of collectors in all their decadent glory, A Noble Madness recounts the saga of the human urge to accumulate, from Caligula to Marie Antoinette, Balzac to Freud, Norman Bates to Andy Warhol. Collectors' love of objects may be mad, even dangerous. But we want to believe their love's a noble madness because by expressing that love, they are themselves"--